2011
DOI: 10.1016/j.smallrumres.2011.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Macromineral requirements for growing Saanen goat kids

Abstract: Chlordecone (Kepone) (CLD) is a highly persistent pesticide which was extensively used in the French West Indies; high levels of CLD can still currently be found in large agricultural areas. As CLD transfers from soil to animals mainly via involuntary ingestion, the consumption of foodstuffs derived from animals raised in contaminated areas may significantly contribute to exposure of humans to CLD. The present study was designed to test the efficacy of two different activated carbons (ACs) sources in limiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
8
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
6
8
2
Order By: Relevance
“…Similar decrease was also reported in cattle (Cheizzotti et al, 2009) and goats (Gomes et al, 2011), which might have been associated with the decreasing growth rate of the bone with maturity (NRC, 2007). …”
Section: Resultssupporting
confidence: 72%
“…Similar decrease was also reported in cattle (Cheizzotti et al, 2009) and goats (Gomes et al, 2011), which might have been associated with the decreasing growth rate of the bone with maturity (NRC, 2007). …”
Section: Resultssupporting
confidence: 72%
“…Additionally, the increase in the net Ca and P requirements for growth estimated in the current study was similar to the pattern of net requirements reported by Gomes et al. () studying male Saanen kids from 5 to 20 kg of BW. Conversely, the net Na and K requirements for empty body weight gain estimated in the present study were greater than those reported by Gomes et al.…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, the net Na and K requirements for empty body weight gain estimated in the present study were greater than those reported by Gomes et al. (). These differences may be related to different environmental conditions (Ammerman and Goodrich, ).…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations